2020
DOI: 10.3390/ijerph17186789
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Illness and Compliance with Therapeutic Recommendations in Patients with Hypertension

Abstract: Arterial hypertension (AH) is one of the most common cardiovascular diseases increasing mortality rates in Poland and worldwide. Due to its prevalence, complications and treatment costs, AH is a significant health-related, economic and social problem. The aim of this study was to assess the level of acceptance of illness and compliance with therapeutic recommendations in patients with AH. The study included 200 outpatient hypertensive patients, 85 men and 115 women aged 49.1 ± 11.6, and used the standardized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
2
15
0
7
Order By: Relevance
“…This study presents a retrospective analysis based on real-world data from a Chinese medicine hospital to investigate the association between non-pharmacological interventions and medication adherence in Our ndings revealed a positive effect of TCM exposure on improving medication compliance in hypertension patients. This observation aligns with previous studies that reported no signi cant relationship between CAM use and medication non-adherence [28,29].Age, sex, and education are recognized factors in uencing adherence in hypertensive patients, while comorbidity has shown a lesser impact [30][31][32][33]. To account for these factors, we included age and sex as independent variables in our GEE model, con rming the consistency of our results.…”
Section: Discussionsupporting
confidence: 91%
“…This study presents a retrospective analysis based on real-world data from a Chinese medicine hospital to investigate the association between non-pharmacological interventions and medication adherence in Our ndings revealed a positive effect of TCM exposure on improving medication compliance in hypertension patients. This observation aligns with previous studies that reported no signi cant relationship between CAM use and medication non-adherence [28,29].Age, sex, and education are recognized factors in uencing adherence in hypertensive patients, while comorbidity has shown a lesser impact [30][31][32][33]. To account for these factors, we included age and sex as independent variables in our GEE model, con rming the consistency of our results.…”
Section: Discussionsupporting
confidence: 91%
“…Illness acceptance will directly affect patients' choice of treatment, thereby affecting their disease health outcomes [30]. Illness acceptance refers to that patients reach a compromise with their disease, accept everything brought by the disease and take positive actions to continue their life [31]. In our study, the score of illness acceptance of IBD patients was lower than that of breast cancer, gastric cancer [32,33].…”
Section: Discussionmentioning
confidence: 56%
“…Another important factor determining a patient’s adjustment to chronic disease is the acceptance of their illness. This is a complex psychological phenomenon, which is of a constructive significance [ 49 ]. In the present study, the time of diagnosis was another factor that influenced “anxious concern”.…”
Section: Discussionmentioning
confidence: 99%
“…Everyone is different; hence, the reaction to the disease and acceptance of the new situation are also different. In the study of Pluta et al, statistical analysis showed that the level of disease acceptance decreased with age ( p = 0.01) [ 49 ]. The highest mean score for disease acceptance was reported in the age group of up to 30 years (34.41 points) and in the age group of 31–40 years (33.3 points).…”
Section: Discussionmentioning
confidence: 99%